Green Marketing Influence: Examining Its Impact On Purchase Decision In Sustainable Halal Cosmetics - Rosidah, Inayatur; Puspitasari, Ratih Hesty Utami; Arsyadi, Muhammad Sani; Putri, Adinda Meilanny (Universitas Nusantara PGRI Kediri, 2024)
Research aim: This study aims to determine the influence of Green Marketing on purchasing literature through brand awareness as a mediator. Design/Methode/Approach: This research used quantitative methods and took a sample of 121 respondents in Semarang who used Wardah halal cosmetics. Data management using SEM. Help. 4.0. The data obtained comes from primary data. The data collection technique using questionnaire distribution is a data collection method that is carried out by giving a collection of questions or written statements to respondents. Research Finding: The result of this study is that based on the composite reliability value of each variable, it is proven that all research variable indicators have a composite reliability value greater than (0.7). And this research that the hypothesis can be accepted and there is a relationship between variables, especially in (Product Green Marketing → Brand Awareness), (Product Green Marketing → Purchase Decision), (Price Green Marketing → Purchase Decision) and (Brand Awareness → Purchase Decision). So, halal cosmetics have a significant effect on the product, price and purchasing decision